Autologous menisci–cruciate ligament composite as a flap for soft tissue reconstruction following malignant bone tumor resection around the knee. (9th January 2023) - Xu, Yu; Li, Yan; Fu, Yiwei; Wang, Bo; Lin, Tiao; Zou, Changye; Huang, Gang; Shen, Jingnan; Yin, Junqiang
Abstract: Background: Despite significant improvements in oncological treatment, the management of soft tissue defects following malignant tumor resection remains challenging. We investigated whether autologous menisci and cruciate ligament, which are traditionally discarded, can be recycled as a supplemental flap in repairing soft tissue defects following malignant bone tumor resection and endoprosthetic reconstruction around the knee. Methods: Four knee specimens were dissected to provide a basis for the design of the menisci–cruciate ligament composite. Then, 40 patients with bone malignancies around the knee were enrolled and underwent reconstruction with free or vascularized composite following malignant tumor resection. The clinical, radiographic, and functional outcomes of this technique were evaluated in >1‐year follow‐up in each patient and compared with 87 patients who suffered from bone malignancies around the knee and were treated by limb salvage but without composite at our center over the same period. During the follow‐up, a composite from one patient who underwent secondary amputation was retrieved and examined for in vivo remodeling. Results: Fourteen patients were treated with vascularized composite transfer (10 distal femurs and 4 proximal tibias) and 26 patients with free composite transfer (19 distal femurs and 7 proximal tibias). The composite can be used to cover the area of soft tissue defect from 22 to 48.38 cm 2 (34.67 ± 6.48 cm 2 ). With contrast‐enhanced ultrasound, peripheral rim healing and dotted blood flow signal at the side of anastomosis were detected on a patient 16 months after free composite transfer. Gross macroscopic remodeling and histopathologic analysis of a retrieved composite also indicated good healing with surrounding tissues and living cells in the composite. The complications and oncologic outcomes were comparable between study and control cohorts, but better Musculoskeletal Tumor Society (MSTS) score for patients reconstructed with composite (26.68 vs. 25.66, p = 0.004). Of note, MSTS score was higher for patients reconstructed with composite at distal femur subdivision compared with the same subdivision in the control cohort (26.97 vs. 25.90, p = 0.009). No statically significant difference was noted in complications, oncologic, and functional outcomes for patients reconstructed with free or vascularized composite. Conclusion: Autogenous menisci–cruciate ligament composite is an alternative option for soft tissue reconstruction. Either vascularized or free composite can be applied, depending on the size and localization of the defect. Abstract : Autologous menisci and cruciate ligament can be recycled as a flap in repairing soft tissue defects following malignant bone tumor resection and endoprosthetic reconstruction around the knee.The recycled composite is safe and provides better Musculoskeletal Tumor Society (MSTS) score.